Management of battery waste recycling by electric motorbike workshops: A literature review - Purwani, Annie; Budijati, Siti Mahsanah; Asih, Hayati Mukti (OPSI, 2024)
Battery waste needs to be managed immediately and thus electric vehicles (EVs) become more popular as a sustainable replacement for internal combustion engine vehicles. This review discusses waste battery recycling industry practices and emphasizes the need for authorized battery management services for electric motorcycles. This gap allows third-party businesses not affiliated with the primary manufacturer to emerge and potentially grow sustainably. The literature review methodology involves an in-depth search of relevant literature using the Scopus database with strategically selected keywords. The VoS Viewer collects, organizes, and graphically maps references to synthesize them orderly. The search initially yielded 138 relevant articles. This number was then narrowed to 66 articles published in English journals. Thirty-nine articles were found when the search was modified to focus on full-text availability. These findings indicate an important need for more targeted research to design effective management frameworks for recycling waste batteries in electric motorbike workshops. All critical components increased waste management awareness and expertise among workshop managers, government policies, funding support, and a well-coordinated supply chain. This assessment identifies barriers to developing a viable battery waste recycling sector and makes recommendations for future policy and research initiatives.